Analisis Hubungan Kecepatan Kapal terhadap Kontrak Sewa Kapal Crew Boat di PT X - Cahya Ire Pusnicha; Bugi Nugraha; Antony Damanik; Intan Sianturi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Ships are used as a mode of transportation, because by using ships all activities will be carried out well and efficiently, and the costs incurred will be smaller than other means of transportation. Crew Boats are ships specifically for transporting company personnel or employees from the coast to offshore locations or buildings. Apart from that, Crew Boats also function as carriers of supporting goods needed to support activities at offshore locations or buildings. Crew Boat ships are certainly not free from problems related to the speed of the ship when rented by the customer, such as how the company determines profits if the speed of the ship does not run according to the ship rental contract that has been agreed and written between the contractor and the customer. The research method used by the author to overcome this problem is a quantitative research method with a descriptive research type. The data analysis method used was correlational analysis using the IBM SPSS Statistics version 26.0 software tool. The data obtained by the author is primary based on a recapitulation of crew boat operations in 2022 at the company PT X., and data collection was obtained based on structured interviews and document studies. The research was carried out for ± 1 month to carry out an analysis of the potential and calculation of ship rentals that occur in crew boat operations. The results of the analysis carried out found that several factors caused a reduction in profits, including below requirement speed. By carrying out speed reconciliation every month by the relevant team, the occurrence of below requirement speeds will be minimized.